Is sex an independent risk factor of in-hospital mortality in patients with burns? A multicentre cohort study from urban India. Issue 1 (January 2022) - Moghe, Dhanashree; Khajanchi, Monty; Gadgil, Anita; Gerdin Wärnberg, Martin; Dev Soni, Kapil; Mohan, Monali; Nobhojit, Roy
Highlights: Females had more than twice the odds of in-hospital mortality from burns compared with males prior to adjustment. After adjusting for variables such as %Total Body Surface Area Burns (%TBSA), age, systolic blood pressure, females were still at a significantly higher odds of death. Other variables significantly associated with mortality from burns in our study were age >65 years and %TBSA. Abstract: Introduction: Globally, nine million people are injured due to fire, heat and hot substances every year with a mortality rate of 1.34%. Research shows conflicting reports regarding sex as a risk factor for mortality in patient with burns. We analysed whether sex is a risk factor for in-hospital mortality in patients admitted with burns in urban India. Methods: A subgroup analysis of patients with burns as mechanism of injury was done from a multi-centre prospective observational study 'Towards Improved Trauma Care Outcomes (TITCO)' in India conducted in October 2013 to December 2015. Results: 1209 patients were identified as having suffered burns from the TITCO study. The mean age was 23 years with 58.9% females. The overall 30 day in-hospital mortality was 574 (48.5%). Among patients who succumbed, 72% were females and 27% were males. We conducted a multivariable logistic regression and found that females were at a significantly higher odds of death compared with males (OR = 1.73 95%CI = 1.06–2.80, p value = 0.02). After performing a sex and age stratified analysis, females in the age group of 15–44 years had a significantly higher number of deaths compared to males in that group. Conclusion: In this multi-center study from urban Indian university hospitals, sex was identified as an independent risk factor of mortality in patients admitted with burns. Females have an increased odds of mortality from burns.